Relationality from attachment to intersubjectivity - Mitchell, Stephen A. 1946-2000 (Abingdon, Oxon New York, NY Routledge, 2022)
This book, first published in the year of the author's death, expresses Mitchell's vision for the theory of Relational Psychoanalysis, and provides his most-developed expression of its foundations. Now republished in this Classic Edition, Mitchell's ideas are brought back to the psychoanalytic readership, complete with a new introduction by Donnel Stern. In his final contribution to the psychoanalytic literature, the late Stephen A. Mitchell provided a brilliant synthesis of the interrelated ideas that describe the relational matrix of human experience. Relationality charts the emergence of the relational perspective in psychoanalysis by reviewing the contributions of Loewald, Fairbairn, Bowlby, and Sullivan, whose voices converge in apprehending the fundamental relationality of the human mind. Mitchell draws on the multiple dimensions of attachment, intersubjectivity, and systems theory in espousing a clinical approach equally notable for its responsiveness and responsible restraint. This remains a canonical text for all relational psychoanalysts and psychotherapists"--
Includes bibliographical references and index.
Keywords: Attachment behavior; Intersubjectivity; Object relations (Psychoanalysis); Psychoanalysis; Psychotherapy